ANALISIS GERAK DAN MAKNA 13 JURUS PENCAK SILAT LIGAR MUSTOFA DI CILEMBANG TASIKMALAYA - Widianingsih, Mudah (Jurnal Seni dan Pembelajaran, 2023)
AbstractThe research aims to analyze the structure of the movement and describe the function of Ligar Mustofa's pencak silat arts. This study uses a qualitative method with an analytic descriptive approach. with data collection techniques using observation, interviews, documentation and literature study. The results of this study are the results of the analysis of the motion of 13 moves which have the meaning of Islamic symbols in each of their movements. This shows that pencak silat has an important use and role in society, especially in developing Islamic preaching which is aimed at the meaning of every movement, as well as fostering a sense of wanting to develop and preserve pencak silat in the younger generation to love their culture and traditional arts more. Thus that this research can provide insight and exposure as a description of the art of pencak silat. Keywords: Analisis, Stucture,Meaning, 13 Kicks Of Pencak Silat